1952
DOI: 10.1111/j.1467-6494.1952.tb01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to Ink Blots under Free and Pressure Conditions*

Abstract: AN THEIR original impact upon American psychology projective techiuques aroused a wave of confused skepticism, but along with this they produced a crisis in psychological theory Here was the startling proposal that by an unbelievably simple procedure it was now possible to reveal the djmamics of the deepest regions of the personality, to get at phenomena which had eluded the complex expenmental and psychometric methods of probing Could it be possible that such a simple technique might succeed where other metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1955
1955
1968
1968

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…These findings indicate that 5s' reaction time behavior in this situation is a general phenomenon, and that M responses individually do not elicit longer reaction times than do individual CF responses. These findings are in agreement with other researches (10,11) which demonstrate that the over-all response set to the Rorschach situation is related to types of responses elicited.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings indicate that 5s' reaction time behavior in this situation is a general phenomenon, and that M responses individually do not elicit longer reaction times than do individual CF responses. These findings are in agreement with other researches (10,11) which demonstrate that the over-all response set to the Rorschach situation is related to types of responses elicited.…”
Section: Resultssupporting
confidence: 93%
“…Other studies in this area have also obtained results suggesting a positive relationship between M production and inhibited motor behavior (5,12). These studies (5,8,10,11,12) have been primarily concerned with movement responses rather than color responses. Thus, while the M:Sum C ratio implies a comparison of two response variables in predicting behavior, research has dealt chiefly with single variables, notably that of human movement.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Turning first to the direct consequences of motor inhibition or delay, two experimental studies have reported increases in Rorschach movement responses of normals following periods of motor inhibition, i.e., standing rigidly in awkward postures or voluntary slow writing (32,48). Another study has investigated the effects of speeding up or slowing down tempos of Rorschach response and has yielded the conclusion that production of M responses is indeed related to tendencies or capacities to delay response (45). Further work remains to be done but it seems clear that so far the linkage of delay of motor discharge and motion perception and imagination can be demonstrated directly in normal adults.…”
Section: Experimental Research With Rorschach's Movement Responsesmentioning
confidence: 99%
“…Lord (19SO) and Sanders and Cleveland (1953) found that examiners who were warm, sympathetic and liked by their subjects obtained significantly more M responses from *This notion is strengthened by Conners' report (personal communication) that one effect of this drug appears to be increased verbalization. them, while Siipola and Taylor (1952) found greater M production under free as opposed to time pressure conditions.…”
Section: Discussionmentioning
confidence: 89%